Chlamydia pneumoniae Infection in Human Monocytes - Airenne, Sari (American Society for Microbiology, 1999)
Chlamydia pneumoniae infection has been associated with cardiovascular diseases in seroepidemiological studies and by demonstration of the pathogen in atherosclerotic lesions. It has the capacity to infect several cell types, including monocyte-derived macrophages, which play an essential role in the development of atherosclerosis. However, the persistence of C. pneumoniae in mononuclear cells is poorly understood. To study the morphology and biological characteristics of the infection, human peripheral blood monocytes were infected with C. pneumoniae. Freshly isolated monocytes resisted the development of infectious progeny, and confocal and transmission electron microscopy showed that the morphology of the inclusions and chlamydial particles was abnormal. Addition of tryptophan or antibodies against gamma interferon did not diminish the inhibition of C. pneumoniae, suggesting that other factors are involved in the chlamydiostatic activity of the monocytes. Chlamydial mRNA was expressed at least 3 days after infection, however, and a capability for infected monocytes to induce a positive lymphocyte proliferative response was detected for up to 7 days, indicating that C. pneumoniae remains metabolically active in the monocytes in vitro. These results are in accordance with the hypothesis that C. pneumoniae may participate in the maintenance of local immunological response and inflammation via infected monocytes and thus enhance atherosclerosis.